Assessment of insulin injection techniques among diabetes patients in a tertiary care centre. (November 2017) - Patil, Milind; Sahoo, Jayaprakash; Kamalanathan, Sadishkumar; Selviambigapathy, Jayakumar; Balachandran, Karthik; Kumar, Ritesh; Vivekanandan, Muthupillai; Ajmal, K.
Abstract: Aims: The efficacy of insulin therapy in diabetes depends on proper storage and injection technique. The purpose of this study was to assess the practice of insulin administration among diabetes patients in a tertiary care center. Materials and methods: This observational study was done in Endocrinology department of a tertiary care center during April–June 2015. The consecutive patients using insulin for at least three months by either syringe or pen were recruited. All of them underwent a survey by the questionnaire which focused on key insulin injection parameters. Results: One hundred and sixty eight (74.67%) patients were storing insulin vials properly. The thigh was the most common site of insulin injection and 209(92.89%) study participants were rotating at the injection sites. Only 48.57% (34/70) subjects were mixing insulin properly before injection. The practice of hand washing and the cleaning of the injection site was practiced by 158(70%) & 171(76.44%) subjects respectively. One hundred and fifty six (69%) patients were injecting with the proper skin fold and 123(55%) subjects were injecting insulin at 90° angle. The majority of patients (91%) were throwing the needle and syringes directly into the garbage and public drainage system. Conclusions: There was a significant gap between the insulin administration guidelines and current insulin injection practice. The diabetic education and counseling about proper insulin injection techniques should be provided to all diabetic subjects.